a derivada função f(x)= 5x³ - 2x² - 6x + 1 é:
Soluções para a tarefa
Respondido por
7
Faz assim :
f(x)= 5x³ - 2x² - 6x + 1
y' = 5x³ = 15x²
y' = 2x² = 4x
y' = 6x = 6
y' = 1 = 0 << derivada da constante é 0.
f(x)'= 5x³ - 2x² - 6x + 1
f(x)'=15x² - 4x - 6
Até mais !
f(x)= 5x³ - 2x² - 6x + 1
y' = 5x³ = 15x²
y' = 2x² = 4x
y' = 6x = 6
y' = 1 = 0 << derivada da constante é 0.
f(x)'= 5x³ - 2x² - 6x + 1
f(x)'=15x² - 4x - 6
Até mais !
Respondido por
3
a derivada é 15x^2 - 4x - 6
Perguntas interessantes
Artes,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás